Síntese do vanadato de manganês pelo método de precipitação e estudo da sua atividade fotocatalítica - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Photocatalysis is part of the Advanced Oxidative Processes. It is possible to use semiconductors that can be excited by visible or ultraviolet radiation, generating radicals that act to degrade organic pollutants. In the present work, manganese vanadate (Mn2V2O7) crystals were synthesized by the homogeneus solution precipitation method with urea as the precipitating agent. The precipitates obtained were submitted to thermal analysis to determine the heat treatment. Subsequently, the samples were structurally characterized by X-Ray Diffraction (XRD) and refinement by the Rietveld method. Transmission Electron Microscopy observed the particle morphologies and investigated the optical properties by Ultraviolet and Visible Absorption Spectroscopy. From the structural analysis, it was possible to determine that from 410 °C/1h, there was the formation of monophasic β- Mn2V2O7 crystals. At 560 °C/1h, a phase transition was observed, referring to the α- Mn2V2O7 phase. From the morphological analysis, it was possible to visualize that the single-phase particles have the shape of plates. These are formed by smaller crystallites, suggesting a growth mechanism by “oriented attachment.” From the characterization by UV-vis spectroscopy, it was possible to calculate the band gap energy of the samples, presenting values between 4.04 and 4.11 eV. The photocatalytic potential of these crystals was investigated. The photocatalytic efficiency was evaluated through the degradation rate of Rhodamine B and Methylene Blue dyes in an aqueous solution in the presence of UVc radiation. The Mn2V2O7 crystals showed low photocatalytic activity, in which degradation was not observed for the rhodamine B dye. The methylene blue dye showed a percentage of 47% degradation in the presence of the catalyst obtained by Method 6
Synthesis of manganese vanadate by precipitation method and study of its photocatalytic activity
Keywords: Catalisadores; Vanadatos; Precipitação (Química); CIENCIAS EXATAS E DA TERRA; Pirovanadato de manganês; Método de precipitação; Atividade fotocatalítica